The Influence of the Social Inclusion-Based Library Transformation Program Implementation on the Image of the Solok Regency Public Library - Tiara Lestari; Elva Rahmah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The Social Inclusion-Based Library Transformation Program (TPBIS) has become an important strategy for strengthening the role of public libraries in community empowerment; however, empirical evidence regarding its influence on library image remains limited. This study aims to analyze the effect of TPBIS implementation on the image of the Solok Regency Public Library. A quantitative approach with an associative design was employed, involving 97 respondents selected through purposive sampling from TPBIS participants. Data were collected using a questionnaire and analyzed through descriptive statistics, simple linear regression, t-test, and coefficient of determination. The findings indicate that both TPBIS implementation and library image were categorized as high, with mean scores of 3.15. The regression analysis shows a positive relationship between TPBIS implementation and library image, as indicated by the equation Y = 0.527 + 0.825X. The t-test confirms a significant effect (p < 0.05), while the coefficient of determination shows that TPBIS implementation contributes 81.6% to library image. These findings suggest that social inclusion-based library programs play a strategic role in enhancing public perceptions of library institutions. This study concludes that effective TPBIS implementation significantly improves the image of the Solok Regency Public Library. The findings contribute to the literature on public library transformation and provide practical implications for library managers and local governments in strengthening institutional reputation, community engagement, and empowerment-oriented library services.